MILITARY EXPENDITURE, ECONOMIC GROWTH AND STRUCTURAL INSTABILITY: A CASE STUDY OF SOUTH AFRICA - Aye, Goodness C.; Balcilar, Mehmet; Dunne, John P.; Gupta, Rangan; Van Eyden, Renee (Taylor & Francis Ltd, 2014)
This paper contributes to the growing literature on the milex-growth nexus, by providing a case study of South Africa and considering the possibility of structural breaks by applying newly developed econometric methods. Using full sample bootstrap Granger non-causality tests, no Granger causal link is found between military expenditure and GDP for 1951-2010, but parameter instability tests show the estimated VARs to be unstable. Using a bootstrap rolling window estimation procedure, however, finds evidence of bidirectional Granger causality in various subsamples. This implies standard Granger non-causality tests, which neither account for structural breaks nor time variation may be invalid.
Keywords: Military spending; Economic growth; Bootstrap; Time varying causality